Informing Canadian Innovation Policy Through a Decolonizing Lens on Indigenous Entrepreneurship and Innovation - Tamtik, Merli (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2020)
While Indigenous entrepreneurship is associated with significant economic promise, Indigenous innovation continues to be invisible in Canadian policy contexts. This article examines how Indigenous entrepreneurial activities are framed in government policy, potentially leading to another wave of active exploitation of Indigenous lands, peoples, and knowledges. The article first discusses the concepts of Indigenous entrepreneurship and innovation through a decolonizing lens, drawing links to education. Then, it provides a set of rationales for why governments need to re-think and prioritize Indigenous entrepreneurship. Next, it maps the current federal government initiatives in this policy sector. Drawing from the Indigenous entrepreneurship ecosystem approach (Dell & Houkamau, 2016; Dell et al., 2017), the article argues that a more comprehensive policy perspective guiding Indigenous entrepreneurship programs should inform Canadian innovation policy. Individual voices from 13 Indigenous entrepreneurs in Manitoba point to three core issues: (a) relationships with the land and the community; (b) the relevance of (higher) education and training; and (c) the importance of cultural survival and self-determination. The article makes an argument for a systemic decolonizing change in how Indigenous innovation is approached in government policyand programs, supported by the work of higher education institutions.